The legal world of the school principal: what leaders need to know about school law - Norton, M. Scott (The Rowman & Littlefield Publishing Group, 2016)
The focus of The Legal World of the School Principal is to emphasize the legal responsibilities of the school principal. This book will help principals be knowledgeable of the court cases and federal and state laws that affect their daily work.